2003
DOI: 10.4049/jimmunol.170.5.2274
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Mast Cell Antimicrobial Activity Is Mediated by Expression of Cathelicidin Antimicrobial Peptide

Abstract: Cathelicidins (caths) are peptides that are expressed at high levels in neutrophils and some epithelia and can act as natural antibiotics by directly killing a wide range of microorganisms. We hypothesized that caths are expressed in mast cells (MCs), because these cells have been previously associated with inherent antimicrobial activity. Cultured murine MCs contained abundant amounts of cathelin-related antimicrobial peptide (AMP), the murine cath, and this expression was inducible by LPS or lipoteichoic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
264
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 354 publications
(269 citation statements)
references
References 22 publications
3
264
0
2
Order By: Relevance
“…The ability of cathelicidin to function as an antimicrobial peptide is required for optimal host defense against infection both in vitro and in vivo (1,24,25). However, recent in vitro studies indicate that cathelicidin can also modulate host inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of cathelicidin to function as an antimicrobial peptide is required for optimal host defense against infection both in vitro and in vivo (1,24,25). However, recent in vitro studies indicate that cathelicidin can also modulate host inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of cathelicidin antimicrobial peptides has been associated with an increase in microbial growth in both mouse models of invasive bacterial infection and in isolated cell culture systems (1,24,25). In addition, a lack of cathelicidin and other antimicrobial peptides correlates with increased infections in patients with atopic dermatitis or Kostman syndrome (19,35).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of mast cells to directly kill bacteria via phagocytosis (Feger et al, 2002) or secretion of antimicrobial peptides has been reported (Di Nardo et al, 2003). To better understand the underlying mechanisms in listerial control, the role of mast cell-mediated phagocytosis in the clearance of L. m. was evaluated.…”
Section: Listeria Monocytogenes Uptake Is Mainly Mediated By Neutrophmentioning
confidence: 99%
“…130 Cathelicidins are antimicrobial peptides that are believed to directly kill microorganisms, participate in the innate immune system, and form a chemical shield of protection on the skin. [130][131][132] LL-37 is the C-terminal part of the only human cathelicidin identified to date, called human cationic antimicrobial protein. 133,134 LL-37 is expressed by polymorphonuclear leukocytes, lymphocytes, macrophages, and epithelial cells.…”
Section: Rosaceamentioning
confidence: 99%